Efektivitas Tiktok Dalam Mempromosikan Tari Zapin Riau Sebagai Upaya Penguatan Identitas Nasional Di Era Digital: Indonesia - Salsa Nouvalia Devega; Diaz Sari; Gerry Julian (INTELEKTUAL ( E-Journal Administrasi Publik dan Ilmu Komunikasi ), 2025)
The ever-growing development of technology in this modern era has had a significant impact on how society conveys and receives information. This phenomenon has a particularly strong influence in Indonesia, as the country is known for its rich cultural diversity. With such cultural diversity, Indonesia faces major challenges in preserving its local culture and maintaining its national identity in the eyes of the world. Technology has made it easy for various kinds of information, including foreign cultures, to enter Indonesia. This has led to a cultural shift where local culture is increasingly neglected. However, by utilizing digital technology wisely and strategically, Indonesia can preserve its culture and identity amidst the influx of foreign cultures. One popular platform in Indonesia today is TikTok. Through this platform, users can create creative videos that can reach audiences worldwide. This makes it much easier to promote local culture. Therefore, this research aims to explore the role of TikTok in the effort to preserve local culture using a qualitative approach through in-depth interviews, observations, and literature studies. The results of this research are expected to provide a deeper understanding and strategic recommendations related to cultural preservation efforts in the digital era.